PEARLS OF WISDOM AND REASONS WHY ZAKAT SHOULD BE MANAGED BY A GOVERNMENT- APPOINTED AMIL INSTITUTION - Nur Hazelen Mat Rusok; Adeeba Najihah Binti Mohd Zaki; Siti Maziah Binti Ab Rahman; Khalid Bin Abdul Wahid (International Journal of Accounting, Finance and Business, 2023)
Zakat is the main tenet on which the Islamic obligation to give alms is built. The difficulties and suffering of the poor should be lessened with the proper and effective zakat institution implementation. The macroeconomic policy requires the government to play a regulatory role in the administration of zakat in a nation. As a qualitative method of data collection for this study, in-depth interviews were used to gather information from Zakat Officer in Majlis Agama Islam and Religious in Kelantan (MAIK). In spite of this, the Amil Institution faces a challenge in trying to streamline and improve the level of professionalism in managing zakat in order to guarantee and protect the zakat asnaf rights, which will increase the community's accountability, trust, and confidence in the Amil Institution. Islam has established eight mustahiq groups for the zakat division. Zakat collectors and distributors (Al-Amil) are two of these groups. Amil is responsible for strategic tasks related to the growth of Zakat in Kelantan. The main themes of this paper will be the aspects of how traditional scholarly opinion regarding the terms of Amil, the classification, duties, and functions of Amil, and best practice recommendations for zakat institutions.